Efficacy of Pneumatic Lithoclast in the Management of Different Metabolic Types of Stones in Lower Ureter - BADICU, GEORGIAN; AZIZ, TASAWAR; TANVEER, NAYAB; RAZZAQ, FOUZIA ABDUL (Pakistan Journal of Medical & Health Sciences, 2025)
Background: Lower ureteric stones are among the most common causes of acute urological emergencies. Pneumatic lithotripsy is a widely used, cost-effective modality for their management. However, the efficacy of pneumatic lithoclast varies based on the metabolic composition of the stones, which may influence fragmentation success and complication rates. Objective: To evaluate the efficacy and safety of pneumatic lithoclast in managing lower ureteric stones of various metabolic compositions and to determine the association between stone type and procedural outcomes. Methods: A prospective clinical study was conducted at the Department of Urology, Jinnah Hospital, Lahore, from June 2022 to Jun 2023. A total of 100 patients with solitary lower ureteric stones were included. All patients underwent semi-rigid ureteroscopy followed by pneumatic lithotripsy. Stone composition was determined postoperatively using Fourier-transform infrared spectroscopy (FTIR). Parameters recorded included stone size, operative time, success of fragmentation, and complication rates. Results: The most common stone type was calcium oxalate monohydrate (34%), followed by uric acid (22%), calcium oxalate dihydrate (16%), mixed stones (12%), struvite (10%), and cystine (6%). Uric acid and calcium oxalate dihydrate stones showed 100% fragmentation success with the shortest operative times (30.3 ± 4.1 min and 37.8 ± 4.5 min, respectively). Cystine and calcium oxalate monohydrate stones had lower success rates (83.3% and 91.2%, respectively) and longer operative durations. The overall fragmentation success rate was 93.4%, with a complication rate of 9.2%, mostly minor. Conclusion: Pneumatic lithoclast is an effective and safe treatment modality for most lower ureteric stones. Stone composition significantly influences fragmentation success and operative duration. Uric acid and calcium oxalate dihydrate stones respond best to pneumatic lithotripsy, while cystine and calcium oxalate monohydrate stones are more resistant. Individualized treatment planning based on preoperative stone assessment may enhance outcomes.